Influence of Hole Geometry on Performance of a Rotational Hydrodynamic Cavitation Reactor - Zhang, Wei; Xie, Chao; Fan, Honggang; Liu, Bing (Frontiers in Energy Research, 2022)
Cavitation is a common phenomenon in hydraulic power industry, ship propulsion, pump station and other industrial fields. In the present work, a high-speed camera is used to visualize the flow field in a rotational hydrodynamic cavitation reactor (RHCR) in a closed cycle test rig, and the numerical simulation is carried out based on the RNG k-ε turbulence model and the Zwart-Gerber-Belamri (ZGB) cavitation model. Influence of hole diameter, hole height and hole cone bottom length on performance of RHCR are comprehensively investigated. The results show that the numerical results are in good agreement with the experimental data, which verifies the accuracy and reliability of the numerical method. The hole diameter mainly influences the water vapor exchange boundary, the hole height mainly influences the cavitation area and intensity, and the cone bottom length mainly influences the vortex number and intensity. Under different hole diameters, the dominant frequent of pressure fluctuation in hole is 24 fi corresponding to the hole number along the circumferential direction, and the maximum amplitude appears near the hole top due to the small gap between the hole top and the side wall of the rotor. When the hole diameter increases from 11 to 17 mm, the pressure fluctuation amplitude increases by 1.65 times for each increase of 2 mm.